Automatic versus manual oxygen titration using a novel nasal high-flow device in medical inpatients with an acute illness: a randomised controlled trial. Issue 1 (6th August 2021) - Harper, James; Kearns, Nethmi; Bird, Grace; Braithwaite, Irene; Eathorne, Allie; Shortt, Nicholas; Weatherall, Mark; Beasley, Richard
Abstract : Background: Guideline recommendations state oxygen should be administered to acutely unwell patients to achieve a target oxygen saturation (SpO2 ) range. The current practice of manual oxygen titration frequently results in SpO2 outside of a prescribed range. The aim of this study was to assess the efficacy of automatic oxygen titration using a closed-loop feedback system to achieve SpO2 within a prescribed target range Methods: An open-label randomised parallel group trial was undertaken comparing automatic oxygen titration using a novel nasal high-flow device to manual oxygen titration using nasal high flow. Medical inpatients requiring oxygen therapy in Wellington Regional Hospital, New Zealand with a prescribed target SpO2 range of 88%–92% or 92%–96% were recruited and randomised equally between the interventions for a period of 24 hours. The primary outcome was the proportion of time spent with SpO2 within the prescribed range. Results: 20 patients were included in the analysis. Automatic oxygen titration resulted in a median (IQR) 96.2% (95.2–97.8) of time within the target range compared with 71% (59.4–88.3) with manual titration; difference (95% CI) 24.2% (7.9% to 35%), p<0.001. There was a reduction in the time spent with SpO2 ≥2% above and ≥2% below range in the automatic titration group, although the point estimate for the differences were small; −1% (−8.2% to −0.04%), p=0.017 and −2.4% (−11.5% to 0.3%), p=0.05 respectively. Conclusions: Nasal high-flow with automatic oxygen titration resulted in a greater proportion of time spent with SpO2 in target range compared with manual titration. Trial registration: The trial was registered with the Australian and New Zealand Clinical Trials Registry (ACTRN12619000901101).